Afghanistan Economic Update, October 2011 - World Bank (Washington, DC, 2017)
Afghanistan's economy is growing strongly. The growth drivers in recent years have been above-average agricultural production, strong growth in construction and transportation, and security spending enabled by large aid flows, especially in FY2009/10. Real Gross Domestic Product (GDP) growth reached 8.4 percent in FY2010/11. Afghanistan's fiscal position is strengthening. In the last three years revenues grew by an average of 34 percent p.a., thanks to improvements in customs and tax administration. Larger increases are expected once mining operations and with the introduction of a value-added tax in FY2014/15. However, government expenditures will also increase in the coming years due to higher security spending, the roll out of pay-and-grading reforms for the civil service, rising recurrent obligations from large donor-supported projects (including those financed outside of the core budget) and the fiscal costs of the Kabul Bank bail-out. The first phase of the handover of security responsibilities to Afghan national security forces in six locations has been completed.